Exploring barriers of childhood full vaccination among children living in Siraro District, West Arsi Zone, Oromia region, Ethiopia: A qualitative study - Guye, Ararso Hordofa; Nigussie, Tadesse; Tesema, Mengistu; Shambi, Dame Banti; Diriba, Berhanu Senbeta; Tefera, Esayas Mekonen; Girma, Yeabsira (Frontiers in Pediatrics, 2023)
Background Childhood immunization is one of the most effective global public health interventions to reduce childhood morbidity and mortality. However, some children remain not fully vaccinated in developing countries due to defaulting from full vaccination, which can put them at risk of acquiring vaccine-preventable disease outbreaks. The barriers to full vaccination were well explored in Ethiopia using a qualitative approach. The study aimed to explore barriers to full childhood vaccination in Siraro District, West Arsi Zone, Oromia, Ethiopia. Methods A qualitative study was conducted in Siraro District through 15 key informant health workers interviews and 6 in-depth interviews with children’s mothers from April 20 to May 15, 2022. Data were collected by semi-structured questionnaires and captured using audio tape recorders and field note-taking. A heterogeneous purposive sampling technique was used to select representative study participants. Data transcription and translation were done according to the respondents’ verbatim from the local language to English. Data coding and key categories were identified and analyzed using thematic analysis. Finally, data were presented in narrative forms using respondents' own words as an illustration. Result Twenty-one study participants were interviewed and included in this study. Of the explored barriers to full childhood vaccination, the evidence from the respondents was integrated from subcategories and presented as a whole within each thematic area. Five thematic areas emerged from interviews of the participants through thematic analysis of the data. The identified barriers were forgetting the next vaccination schedule, migration of parents, work overload, lack of knowledge and awareness, rumors, and misinformation. Additionally, vaccination service delivery-related barriers such as vaccine vials not being opened for a few children, fear of vaccine side effects, closed health posts during visits by mothers for vaccination, and absence of health extension workers at health posts were the key barriers to full childhood vaccination. Conclusion Forgetting vaccination schedule, migration of parents, work overload, rumors, and misinformation, fear of vaccine side effects, vaccine vial not opened for few children, closed health posts during visiting by mothers, absence of health extension workers from health posts were the key barriers to the full vaccination status of children. Thus, the district health office should work on barriers to full vaccination by strengthening vaccination service delivery and improving vaccination awareness through a health extension program.